THE FUTURE OF MALAYSIA TRADE IN ONE BELT ONE ROAD - Woan-Lin, Beh; Wai-Mun, Har; Shyue-Chuan, Chong; Sim-Kuen, Lee (International Journal of Supply Chain Management, 2018)
The One Belt and One Road Initiative (OBOR) will open up more trade opportunities for Malaysia due to the two trade routes, namely, the land-based Silk Road Economic Belt and the seagoing 21st Century Maritime Silk Road . This paper empirically examines the short-term and long-term relationship between Malaysia s trade balance, real exchange rates (RER), industry production index (IPI), Malaysia s consumer price index (MCPI) and China s consumer price index (CCPI) for the period January 2000 to September 2017. The Malaysia s trade balance is regarded as an explained variable while the MYR-RMB, IPI, MCPI and CCPI will be regarded as explanatory variables. The Autoregressive Distributed Lag (ARDL) cointegration test is employed to estimate the long-run relationship between China and Malaysia. Then the Error-Correction model and the error correction term would explain the speed of adjustment in restoring equilibrium in the dynamic model referred to in this paper. The finding shows that the exports in Malaysia would benefit from the real appreciation of MYR and China s inflation. The OBOR will open up more opportunities for Malaysia to generate trade mainly because it involves the belt and the maritime but diplomatic relationship and export constructive policy also important to improve Malaysia trade balance with China